2020
DOI: 10.1128/aac.02093-19
|View full text |Cite|
|
Sign up to set email alerts
|

A Population Pharmacokinetics and Pharmacodynamic Approach To Optimize Tazobactam Activity in Critically Ill Patients

Abstract: The percentage of the time that the free drug concentration remains above a concentration threshold (%fT > concentration threshold) has frequently been identified to be the optimal pharmacokinetic (PK)-pharmacodynamic (PD) target of interest for tazobactam using in vitro infection models. Similar in vitro models suggested that an 85% fT > concentration threshold of 2 μg/ml for tazobactam is required to demonstrate a 2-log10-unit decrease in the number of CFU per milliliter from that at the baseline at 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
2
10
1
Order By: Relevance
“…Considerably less is known about the pharmacokinetics of tazobactam in critically ill patients. The typical total clearance for tazobactam was estimated to be higher (10.3 L/h, 95% CI 9.1–11.7 L/h) than reported in a small study in critically ill patients (5.3 L/h, 95% CI 2.2–9.1 L/h), but similar to reported in patients undergoing colorectal surgery (11.3 L/h, 95% CI 5.1–17.4 L/h) [ 14 , 28 ].…”
Section: Discussionsupporting
confidence: 77%
“…Considerably less is known about the pharmacokinetics of tazobactam in critically ill patients. The typical total clearance for tazobactam was estimated to be higher (10.3 L/h, 95% CI 9.1–11.7 L/h) than reported in a small study in critically ill patients (5.3 L/h, 95% CI 2.2–9.1 L/h), but similar to reported in patients undergoing colorectal surgery (11.3 L/h, 95% CI 5.1–17.4 L/h) [ 14 , 28 ].…”
Section: Discussionsupporting
confidence: 77%
“…Because tazobactam has only bacteriostatic activity, the proportion of dosing interval above the minimum effective concentration (MEC) was calculated. The PTA for 63% f T > 2 mg/L of free tazobactam was evaluated, and the acceptable PTA level was set at ≥50% ( 30 , 31 ).…”
Section: Methodsmentioning
confidence: 99%
“…For strains expressing higher levels of beta-lactamase, TA was defined as concentrations above 2 mg/L free tazobactam for 85% of the dosing interval. A model was created using data from 18 critically ill patients, and demonstrated that a TZP 16/2 g CI/day would result in >75% TA for tazobactam [27]. Further, 16/2 g CI/day would also result in adequate alveolar concentrations of piperacillin and tazobactam [28].…”
Section: Penicillinsmentioning
confidence: 99%